Relação entre atividade física no lazer e burnout em trabalhadores da indústria - Gorski, Gabriela Martins (2015)
The aim of this study is to examine the relationship between physical activity during leisure time and dimensions of burnout syndrome among industrial workers. Was used to characterize the sample a structured questionnaire with age, gender, marital status, health perception and educational level. Measuring the risk of burnout was performed using the Maslach Burnout Inventory - General Survey (MBI-GS) and the level of physical activity during leisure time, occupational and commuting was conducted through the questionnaire on habitual physical activity Baecke. The participants were 150 male employees with a predominance of individuals aged 20-29 years who have studied the complete high school, married and with a perception of excellent health / very good. The results indicated a moderate risk of developing burnout syndrome in three dimensions and a less favorable situation as the practice of physical activity. The dimensions of burnout showed no statistically significant differences for individual characteristics, however statistically significant difference in the perception of health as they relate to occupational physical activity, physical exercise in leisure and total score of physical activity, and for the variable schooling when related to exercise physical leisure and total score of physical activity. The relationship between the dimensions of physical activity and the dimensions of burnout syndrome, showed a significant positive correlation between occupational physical activity and emotional exhaustion and negative between depersonalization and exercise play. It follows that the more physical activity workers perform when you work, the greater emotional exhaustion he will, and the more exercise the worker held in their leisure time, the lower the risk that it develops the burnout syndrome, specifically the dimension depersonalization. Therefore, we suggest new studies that relate to burnout and physical activity in various fields, mainly held at leisure in various working classes, especially the industrial, in order to seek to bridge the gap that exists in the literature on this topic because this is an important discussion with regard to the health and quality of worker's life.